2016
DOI: 10.1007/s10517-016-3560-6
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Proliferative Activity of Mesenchymal Stem Cells in 3D Polylactide Scaffolds Depends on Cell Seeding Technique and Collagen Modification

Abstract: We analyzed viability of mesenchymal stem cells seeded by static and dynamic methods to highly porous fibrous 3D poly-L-lactide scaffolds with similar physical and chemical properties, but different spatial organization modified with collagen. Standard collagen coating promoted protein adsorption on the scaffold surface and improved adhesive properties of 100 μ-thick scaffolds. Modification of 600-μ scaffolds with collagen under pressure increased proliferative activity of mesenchymal stem cells seeded under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…These effects might be masked in our approach by collagen coating. Rodina tested migration and proliferation of murine mesenchymal stem cells on electrospun PLA scaffolds coated with collagen [ 41 , 42 ]—completely different to our scaffolds, but their study demonstrates possible combination of PLA and collagen. Concerning biocompatibility of PLA, our study is in accordance with the described literature, however, it is the first study analyzing 3D-printed PLA discs coated with collagen with different human cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…These effects might be masked in our approach by collagen coating. Rodina tested migration and proliferation of murine mesenchymal stem cells on electrospun PLA scaffolds coated with collagen [ 41 , 42 ]—completely different to our scaffolds, but their study demonstrates possible combination of PLA and collagen. Concerning biocompatibility of PLA, our study is in accordance with the described literature, however, it is the first study analyzing 3D-printed PLA discs coated with collagen with different human cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al have observed intermediate degrees of spreading and proliferation of vascular smooth muscle cells on an engineered model ECM consisting of fibrillary type I collagen and fibronectin compared to the cellular responses measured on collagen or fibronectin alone [ 57 ]. By investigating the migratory and proliferative activity of mesenchymal stem cells on 3D polylactide scaffolds, Rodina et al have concluded that larger pore size or higher porosity of the scaffold enhances the cellular penetration and growth [ 58 , 59 ]. Chemical, micron- and/or nano-scale topographical analyses of the matrices have not been performed in the present study and deserve detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, these data were in accord with the improved results in 3D fibrous scaffolds for cell culture and tissue engineering compared to 2D cultures reported in recent years. [39][40][41][42][43] The fibrous structure in these materials was designed to mimic ECM properties, resulting in an increase in desired cell response. However, as the synthetic polymers used in our culture assays were non-native to the cells, we anticipated that peptide or protein incorporation or functionalisation would be required to overcome some key practical challenges.…”
Section: Enzymatic-free Passagingmentioning
confidence: 99%
“…These included poor cell attachment and induction of inflammation or undesired cell differentiation due to the suboptimal mechanical or chemical properties (such as stiffness and hydrophobicity) of conventional polymer fibres. [39][40][41][42][43] For example, Rodina et al 42 investigated migration and proliferation of mesenchymal stromal stem cells (MSSCs) on collagen protein modified PLA fibrous scaffolds. They observed more uniform distribution and cell penetration into these modified scaffolds.…”
Section: Enzymatic-free Passagingmentioning
confidence: 99%